2019
DOI: 10.3390/nu11010157
|View full text |Cite
|
Sign up to set email alerts
|

A Plant-Based Meal Increases Gastrointestinal Hormones and Satiety More Than an Energy- and Macronutrient-Matched Processed-Meat Meal in T2D, Obese, and Healthy Men: A Three-Group Randomized Crossover Study

Abstract: Gastrointestinal hormones are involved in regulation of glucose metabolism and satiety. We tested the acute effect of meal composition on these hormones in three population groups. A randomized crossover design was used to examine the effects of two energy- and macronutrient-matched meals: a processed-meat and cheese (M-meal) and a vegan meal with tofu (V-meal) on gastrointestinal hormones, and satiety in men with type 2 diabetes (T2D, n = 20), obese men (O, n = 20), and healthy men (H, n = 20). Plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…In this regard, subjects who follow a PBD tend to show lower LDL-C values than omnivores [ 187 , 188 ]. In a three-group randomized crossover study performed in 60 subjects that followed a PBD, this dietary model increased postprandial secretion of gastrointestinal hormones, as well as promoting satiety, compared to diets with processed meat and cheese, both in healthy, obese, and diabetic men [ 189 ]. Thus, these properties could have practical implications for the management of hypertriglyceridemia in some metabolic conditions.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…In this regard, subjects who follow a PBD tend to show lower LDL-C values than omnivores [ 187 , 188 ]. In a three-group randomized crossover study performed in 60 subjects that followed a PBD, this dietary model increased postprandial secretion of gastrointestinal hormones, as well as promoting satiety, compared to diets with processed meat and cheese, both in healthy, obese, and diabetic men [ 189 ]. Thus, these properties could have practical implications for the management of hypertriglyceridemia in some metabolic conditions.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Mechanistically, an explanation might come from differences in gastrointestinal hormone secretion and satiety sensations depending on the protein’s source. In a 60 male adult patient intervention, with a type II diabetes group, a BMI and age-matched group and an age-matched, healthy group, giving two test burgers containing tofu or meat and cheese at a one-week interval, in random order, led to higher satiety feeling, post prandial GLP1 and amylin levels in the group that took tofu [ 40 ]. Since GLP1 and amylin are hormones involved in the pathway inducing satiety, this might partially explain the effect of vegetable proteins on body weight.…”
Section: Using Proteins To Treat Obesitymentioning
confidence: 99%
“…In a previous clinical interventional study, a vegetarian diet led to greater weight loss and improved glycaemic control, insulin resistance and oxidative stress markers compared to a conventional hypocaloric diet [11]. Furthermore, our previous randomised crossover study reported that a plant-based meal increased postprandial secretion of gastrointestinal hormones more effectively than a proceseed meat meal in obese and T2D men [12]. Another study found improvements in postprandial incretin and insulin secretion after a plant-based meal in T2D patients, highlighting the therapeutic potential of this type of diet in improving b-cell function [13].…”
Section: Introductionmentioning
confidence: 88%